Extended p-adic q-invariant integrals on ℤp associated with applications of umbral calculus - Araci, Serkan; Acikgoz, Mehmet; Kilicman, Adem (SpringerOpen, 2013)
The fundamental aim of this paper is to consider some applications of umbral calculus by utilizing from the extended p-adic q-invariant integral on ℤp. From those considerations, we derive some new interesting properties on the extended p-adic q-Bernoulli numbers and polynomials. That is, a systemic study of the class of Sheffer sequences in connection with generating function of the p-adic q-Bernoulli polynomials are given in the present work.